Experiences conducting systematic reviews from novices' perspective - Riaz, Mehwish; Sulayman, Muhammad; Salleh, Norsaremah; Mendes, Emilia (British Computer Society, 2010)
Background: A systematic review (SR) is a sound methodology for collecting evidence on a research topic of interest and establishing the context of future research. Unlike ordinary or even expert literature reviews, SRs are systematic thus increasing the confidence in the findings from the previous published literature. SRs can be carried out by both experienced and novice researchers; however, while expert researchers‟ experiences with conducting SRs are important for improving the SR body of knowledge, we believe that novice researchers‟ experiences are equally important to establish what distinct problems they face while carrying out SRs. With a prior knowledge of these issues, novice researchers can better plan their SRs and seek guidance from expert researchers. Aim: The aim of this paper is therefore to report on experiences conducting SRs from the perspective of novice researchers. The paper reports first hand experiences of novices conducting SRs and compares them with the experiences of an expert as well as with the experiences reported in the previous literature. Method: An instrument was created and used to gather the experiences conducting SRs from three PhD students and their supervisor. The instrument covered all the SR steps; it was individually filled out by each of the participating subjects and its data was later on aggregated. Results: The results show that the problems faced by novices in terms of time taken to conduct the review; defining the research questions, inclusion/exclusion criteria, data extraction and data synthesis forms are not faced by expert researchers. Moreover, problems faced by novices related to defining quality criteria are different in nature than those faced by expert researchers. Conclusions: It has been observed that while numerous problems are faced by both novices and experts, many others are specific to novices, where several of these can be solved with the help of domain and SR experts.